Catalytic Asymmetric Mannich/Cyclization of 2‑Isothiocyanato-1-indanones: An Approach to the Synthesis of Bispirocyclic Indanone–Thioimidazolidine–Oxindoles - Zhao, Bo-Liang; Du, Da-Ming (Organic letters, 2018)
This study demonstrates that novel isothiocyanates derived from 1-indanones are useful building blocks in heteroannulation reactions with isatinimines. This convenient Mannich/cyclization cascade reaction serves as a powerful tool for the enantioselective construction of bispirocyclic indanone–thioimidazolidine–oxindoles bearing two adjacent spiro-quaternary stereocenters in good to excellent yields with excellent diastereo- and enantioselectivities. Versatile transformations of the products into other potential bioactive bispirocyclic heterocycles have also been demonstrated.